EFAKTIVITAS DANA BOS DALAM PENINGKATAN KUALITAS PENDIDIKAN DI KOTA BEKASI: ANALISIS IMPLEMENTASI, TANTANGAN DAN STRATEGI PERBAIKAN - Galuh nugraheni; Norman Rade Arfiansyah; Ernani Yunita; Eriyatuzzahro; Aprilliantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study explores the strategic potential of waqf as a sustainable financing mechanism for education in the era of globalization. Conventional funding sources such as government budgets and community contributions are often insufficient to support the increasing demands for high-quality and equitable education. Through a qualitative literature review, this research analyzes scholarly articles, books, institutional reports, and regulatory documents related to waqf management and educational financing. The findings demonstrate that waqf has historically functioned as a foundation for educational development, supporting infrastructure, scholarships, research, and institutional sustainability. In the modern context, innovative models such as cash waqf, waqf sukuk, and digital waqf platforms further expand its potential role. However, challenges persist, including low waqf literacy, weak managerial capacity among nazir, and limited transparency in governance. This study concludes that optimizing waqf for educational financing requires strengthened governance, digital innovation, professional management, and enhanced public literacy. Properly developed, waqf can serve as a long-term, stable, and inclusive financial pillar for education amid global challenges. Keywords: Waqf, Educational Financing, Globalization, Cash Waqf, Islamic Philanthropy;